Prognostic impact of cachexia by multi‐assessment in older adults with heart failure: FRAGILE‐HF cohort study - Emi Maekawa; Takumi Noda; Daichi Maeda; Masashi Yamashita; Shota Uchida; Nobuaki Hamazaki; Kohei Nozaki; Hiroshi Saito; Kazuya Saito; Yuki Ogasahara; Masaaki Konishi; Takeshi Kitai; et al. (Wiley, 2023)
Abstract Background Cachexia substantially impacts the prognosis of patients with heart failure (HF); however, there is no standard method for cachexia diagnosis. This study aimed to investigate the association of Evans's criteria, consisting of multiple assessments, with the prognosis of HF in older adults. Methods This study is a secondary analysis of the data from the FRAGILE‐HF study, a prospective multicentre cohort study that enrolled consecutive hospitalized patients aged ≥65 years with HF. Patients were divided into two groups: the cachexia and non‐cachexia groups. Cachexia was defined according to Evans's criteria by assessing weight loss, muscle weakness, fatigue, anorexia, a decreased fat‐free mass index and an abnormal biochemical profile. The primary outcome was all‐cause mortality, as assessed in the survival analysis. Results Cachexia was present in 35.5% of the 1306 enrolled patients (median age [inter‐quartile range], 81 [74-86] years; 57.0% male); 59.6%, 73.2%, 15.6%, 71.0%, 44.9% and 64.6% had weight loss, decreased muscle strength, a low fat‐free mass index, abnormal biochemistry, anorexia and fatigue, respectively. All‐cause mortality occurred in 270 patients (21.0%) over 2 years. The cachexia group (hazard ratio [HR], 1.494; 95% confidence interval [CI], 1.173-1.903; P = 0.001) had a higher mortality risk than the non‐cachexia group after adjusting for the severity of HF. Cardiovascular and non‐cardiovascular deaths occurred in 148 (11.3%) and 122 patients (9.3%), respectively. The adjusted HRs for cachexia in cardiovascular mortality and non‐cardiovascular mortality were 1.456 (95% CI, 1.048-2.023; P = 0.025) and 1.561 (95% CI, 1.086-2.243; P = 0.017), respectively. Among the cachexia diagnostic criteria, decreased muscle strength (HR, 1.514; 95% CI, 1.095-2.093; P = 0.012) and low fat‐free mass index (HR, 1.424; 95% CI, 1.052-1.926; P = 0.022) were significantly associated with high all‐cause mortality, but there was no significant association between weight loss alone (HR, 1.147; 95% CI, 0.895-1.471; P = 0.277) and all‐cause mortality. Conclusions Cachexia evaluated by multi‐assessment was present in one third of older adults with HF and was associated with a worse prognosis. A multimodal assessment of cachexia may be helpful for risk stratification in older patients with HF.